Respostas

2014-01-26T10:35:43-02:00
Resposta

Sen 90º

sen ( a + b) = senA*cosB + senB*cosA

sen (45+45) = sen45*cos45 + sen45*cos45

sen 90º = √2/2*√2/2 + √2/2*√2/2

sen90º = √4/4 + √4/4

seno 90º = 2/4 + 2/4

seno 90ª = 4/4

seno 90º = 1

Cosseno 90º

cos ( a + b) = cosA*cosB - senA*senB

cos ( 45 + 45 ) = √2/2*√2/2 - √2/2*√2/2

cos 90º = √4/4 - √4/4

cos 90º = 2/4 - 2/4

cos 90º = 0
obrigada madilolages
de nada.
no cosseno de 90° a formula ta + e na conta ta - e isso msm
Sim é isso mesmo; cos ( a + b) = cosA*cosB - senA*senB
ha ta